Shear strengthening of steel I-beams by using CFRP strips - Narmashiri, K.; Jumaat, Mohd Zamin; Sulong, N.H.R. (Scientific Research and Essays, 2010)
Normally, carbon fiber reinforced polymer (CFRP) strips have been used for flexural strengthening of steel beams, but in this research, application of CFRP strips as shear reinforcements was innovated. In this novel method, investigation on the requirement of applying CFRP on one or both sides of the web, and using different values of CFRP area on the web were the two main objectives. In this research, five specimens were selected. The first specimen (B1) was not strengthened. The second and third beams (B2 and B3) were upgraded on both sides of web with the CFRP ratios of 0.72 and 0.48, respectively. The fourth and fifth specimens (B4 and B5) were strengthened on one side of web with the CFRP ratios of 0.72 and 0.48, respectively. Both numerical simulation and experimental test were used in this research. The results show that by using CFRP strips on web, could appropriately increased the load bearing capacity up to 51. Also, the CFRP ratios of 0.72 and 0.48 for both sides of web have produced the same load capacity. Using less CFRP in the shear zone with the same load capacity of the steel I-beams was one of the significant achievements of this research.